Fatigue behaviour of alumina-fibre-reinforced epoxy resin composite pipes under tensile and compressive loading conditions - Srivastava V.K.; Kawada H. (My University, 2025)
Fatigue tests have been conducted on composites consisting of epoxy resin reinforced with alumina fibres (AFRP) under cyclic tensile and compressive loading conditions with the variation of fibre orientation. The behaviour of the stress/strain curve for a ±45° sample is different from those for the ±15 and ±25° composite specimens, whereas, the monotonic strength decreases with increase in fibre angle for all specimens, which satisfies the maximum stress failure criterion. Fatigue results show that the applied stress decreases with an increase in the number of cycles to failure under both loading conditions for all composite pipes, but for the ±45° sample the decrease was slow. The results of fatigue tests on a macroscopic level indicate that the matrix crack density slowly increased with increase in the normalized number of cycles to failure in all the specimens. The normalized apparent stiffness therefore falls with an increase of the normalized number of cycles to failure. However, the maximum stress decreased with the increase in the number of cycles to failure in the case of the ±45° pipe. Finally, it is observed that matrix cracking and delaminations are occuring in the ±45° sample whereas delamination and fibre buckling are appearing in the ±15 and ±25° samples. © 2001 Elsevier Science Ltd. All rights reserved.